Distributed generation system control strategies with PV and fuel cell in microgrid operation. (August 2016) - Bai, Wenlei; Abedi, M. Reza; Lee, Kwang Y.
Abstract: Control strategies of distributed generation (DG) are investigated for different combination of DG and storage units in a microgrid. In this paper the authors proposed a microgrid structure which consists of a detailed photovoltaic (PV) array model, a solid oxide fuel cell (SOFC) and various loads. Real and reactive power (PQ) control and droop control are developed for microgrid operation. In grid-connected mode, PQ control is developed by controlling the active and reactive power output of DGs in accordance with assigned references. Two PI controllers were used in the PQ controller, and a novel heuristic method, artificial bee colony (ABC), was adopted to tune the PI parameters. DGs can be controlled by droop control both under grid-connected and islanded modes. Droop control implements power reallocation between DGs based on predefined droop characteristics whenever load changes or the microgrid is connected/disconnected to the grid, while the microgrid voltage and frequency is maintained at appropriate levels. Through voltage, frequency, and power characteristics in the simulation under different scenarios, the proposed control strategies have demonstrated to work properly and effectively. The simulation results also show the effectiveness of tuning PI parameters by the ABC. Highlights: We proposed a microgrid structure which consists of a detailed photovoltaics (PV), solid oxide fuel cell (SOFC) to supply various loads. PQ control and droop control were developed for proper microgrid operation under grid-connected mode and island mode. A heuristic method called artificial bee colony (ABC) was proposed to find the control parameters.